The Role of Komunitas Guru Bahasa Inggris Konawe Utara in English Teacher’s Professional Development - Masniani Masniani; Asrun Lio; Aderlaepe Aderlaepe (Journal of Language Education and Educational Technology (JLEET), 2024)
This study delves into the pivotal role played by Komunitas Guru Bahasa Inggris Konawe Utara in advancing the professional growth of English teachers, particularly among its members, while also shedding light on the hurdles they encounter. Utilizing qualitative research methods, the study engaged with 21 community members. Results underscore the substantial impact of the community in facilitating the development of teaching materials such as lesson plans and syllabi, enhancing teachers' performance in assessments like UKG, facilitating access to various professional development avenues, and fostering collaborations with other esteemed professional bodies like PGRI, IGI, and SGI. However, amidst these positive contributions, the study unearths a spectrum of challenges faced by English teachers when endeavoring to partake in professional development activities. These obstacles encompass the absence of requisite qualifications, experience, or seniority; financial constraints impeding participation due to the exorbitant costs associated with professional development initiatives; insufficient support from employers; conflicts arising between professional development opportunities and work commitments; time constraints stemming from familial responsibilities; and a dearth of tailored and suitable professional development options. In light of these findings, it is imperative to integrate an understanding of these challenges into the planning and execution of future professional development initiatives tailored to English teachers.